Thothokkêrot : cerita rakyat sebagai sumber penelitian sejarah - Timoer, Soenarto, 1922- (Balai Pustaka, 1981)
The use of folktales for historical reconstruction; the case of Thothokkerot as depicted in ancient Javanese manuscripts.